Social support and risk perception of influenza among Chengdu residents: A cross-sectional study during post-pandemic recovery - Cheng Yang; Jiawei Li; Qin Zeng; Xianqiong Feng (PLoS ONE, 2025)
Influenza remains a global public health threat, yet limited evidence exists regarding public risk perception and social support dynamics in post-pandemic contexts. This study investigates the interplay between social support and influenza risk perception among residents in Chengdu, China, following the ease of COVID-19 restrictions. A cross-sectional survey was conducted from January to March 2024 using convenience sampling (n = 708). Validated tools included the Social Support Rating Scale (SSRS) and a researcher-developed Risk Perception Scale (RPS). Data were analyzed via Kruskal-Wallis tests and Spearman correlations using SAS 9.4 and SPSS 26.0. The results showed moderate median social support (37 points; 63.79% of maximum score) but alarmingly low risk perception (36 points; 40.0% of maximum score). Younger adults (<25 years) and older adults (>40 years) demonstrated significantly higher risk perception than middle-aged groups (P < 0.01). Healthcare workers exhibited substantially lower risk perception than students (P < 0.01). A weak but significant negative correlation emerged between social support and risk perception (r=−0.125, P < 0.01), with the strongest negative correlation observed for risk familiarity perception (r=−0.171, P < 0.01). Critically, Chengdu residents displayed inadequate risk awareness of influenza severity (score rate = 32%, very low) and familiarity (score rate = 36.7%, low), potentially undermining prevention efforts. Targeted health campaigns emphasizing risk communication (particularly for healthcare workers and middle-aged residents) and social resource mobilization are urgently needed to address these deficits.